2019
DOI: 10.4103/jmss.jmss_52_18
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of skin repigmentation using a multilayer perceptron

Abstract: Background: Vitiligo is a pathology that causes the appearance of achromic macules on the skin that can spread on to other areas of the body. It is estimated that it affects 1.2% of the world population and can disrupt the mental state of people in whom this disease has developed, generating negative feelings that can become suicidal in the worst of cases. The present work focuses on the development of a support tool that allows to objectively quantifying the repigmentation of the skin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The classic Kohonen network training procedure is an adjustment of synaptic weights without taking into account other network learning options such as the type and parameters of the membership function and network architecture. There is additional training of artificial neural networks, which was not taken into account in [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]:…”
Section: Materials and Methods Of The Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The classic Kohonen network training procedure is an adjustment of synaptic weights without taking into account other network learning options such as the type and parameters of the membership function and network architecture. There is additional training of artificial neural networks, which was not taken into account in [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]:…”
Section: Materials and Methods Of The Researchmentioning
confidence: 99%
“…2 shows the proposed algorithm for artificial neural network training. Improvement of the specified training algorithm consists in adding actions 3-8 to the known methods of training artificial neural networks.There is additional training of artificial neural networks, which was not taken into account in[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]:-learning the architecture of artificial neural networks, depending on the amount of input information (number of…”
mentioning
confidence: 99%
“…The analysis of scientific works [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] showed that well-known training methods are used for artificial neural networks. These methods are usually focused on training synaptic weights or membership functions.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…DSS are actively used in processing large data sets, providing information support to the decision-making process of decision-makers. The basis of existing DSS is artificial intelligence methods [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of scientific papers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] has revealed that known methods for training artificial neural networks have the following shortcomings:…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%